UNVEILING THE POLITICAL IMPACT OF FAST FASHION CONSUMPTION: THE ROLE OF LOWER MIDDLE CLASS IN ENVIRONMENTAL CRISIS IN INDONESIA? - Hajad, Vellayati; Herizal, Herizal; Ikhsan, Ikhsan; Setiawan, Deni; Handayani, Sri Wahyu (Universitas Padjadjaran, 2024)
ABSTRACT. This article delves into the impact and role of the lower middle class on Indonesia’s environmental landscape. Despite their social and economic marginalization, this demographic heavily relies on cheap, easily accessible fast fashion for clothing, leading to detrimental environmental consequences such as ecosystem degradation and pollution. This research was carried out by conducting a literature review through library research, where the data came from library data collection. This study further analyzes literature regarding socio-economic dynamics and environmental problems. This approach unveiled the lower middle class’s profound influence of fast fashion consumption on Indonesia’s environment. The research highlights the lower middle class’s pivotal role in fast fashion waste distribution, exacerbating environmental pollution. Hence, governmental intervention becomes imperative to regulate fast fashion production, manage waste, and restrict the influx of second-hand fast fashion businesses. The article concludes by emphasizing the lower middle class’s dual role as both major consumers and victims of global capitalism in the fast fashion industry, necessitating state protection through various policy measures. These include elevating product quality standards, ensuring fair labor practices, enhancing consumer protection, and controlling the influx of foreign fast fashion products. Ultimately, the study underscores the necessity of comprehensive governmental interventions to mitigate the environmental repercussions of fast fashion consumption, safeguarding both the lower middle class and Indonesia’s environment.